Pertumbuhan Akar Anggrek Bulan Melalui Sistem Tanam Hidroponik dalam Smart and Aesthetic Greenhouse - Ayu Ratna Permanasari; Harita Nurwahyu Chamidy; Robby Sudarman; Dianty Rosirda; Mochammad Machmud Rifadil; Wahyu Wibisono (Jurnal Serambi Engineering, 2024)
Hydroponic orchid (Phalaenopsis) growing is a modern agricultural technique that is growing in popularity due to its ability to produce high quality orchid plants with efficient use of resources. Hydroponics is an agricultural method that does not use soil media, but rather nutrient solutions specially formulated to meet the nutritional needs of plants. In orchid cultivation, hydroponics offers several advantages, including more precise nutrient control, a more sterile growing environment, and a reduced risk of soil-borne pests and diseases. The aim of this study was to investigate the effectiveness of the hydroponic method in orchid cultivation, focusing on vegetative growth, flower quality and the efficiency of water and nutrient use. The results of the study showed that orchids grown hydroponically had faster growth and better flower quality compared to conventional methods. The average growth of orchid roots in the aquaponic system was 2mm per week and the growth of orchid roots without hydroponics was approximately 1.3mm per week.